Recognizing some geometrical objects from a discrete set of polygons - Huy, Ngô Hoàng; Tạo, Ngô Quốc (Journal of Computer Science and Cybernetics, 2016)
This paper presents a post - processing method for extracting polygons after vectorization processing. These polygons are used for a Spatial Data Type of Geographic Information Systems or for recognizing primitive objects included in technical drawings. We propose the semi - automatic searching method for extrating from a set of polylines to a polygon surrounding a given point. This method is based on the depth searching strategy. Then we give a measure fitting polygons with primitive geometrical objects. In fact, the paper makes a deal with the applying of global statistical and geometrical invariants for reconizing planar objects. Nhận dạng một số đối tượng hình học từ các tập đường gấp khúc rời rạc